IMPROVING THE PROCEDURE FOR CALCULATING AND PAYING EXCISE TAX IN UZBEKISTAN (World Economics and Finance Bulletin, 2023)
The excise tax calculation and payment process in Uzbekistan is an important source of revenue for the government, but it can be improved to make it more efficient and transparent. To improve the current process, several procedures can be implemented, including simplifying the calculation process, providing clear guidance, increasing taxpayer education and training programs, implementing an efficient electronic system, and providing incentives for timely payments. By implementing these procedures, Uzbekistan can increase compliance among taxpayers and collect taxes more efficiently, resulting in increased revenue for the government.
Keywords: Excise tax; calculation; payment process